Toric Ideals of Finite Graphs and Adjacent 2-Minors - Ohsugi, Hidefumi; Hibi, Takayuki (MATHEMATICA SCANDINAVICA, 2014)
We study the problem when an ideal generated by adjacent $2$-minors is the toric ideal of a finite graph.